Senegal : 2002 Article IV Consultation and Requests for a Three-Year Arrangement Under the Poverty Reduction and Growth Facility and for Additional Interim Assistance Under the Enhanced Initiative for Heavily Indebted Poor Countries. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2003)
This paper examines Senegal's 2002 Article IV Consultation and Requests for a Three-Year Arrangement Under the Poverty Reduction and Growth Facility (PRGF) and for Additional Interim Assistance Under the Enhanced Initiative for Heavily Indebted Poor Countries. Overall, economic developments in 2002 were mixed. Real GDP growth decelerated to 2.4 percent in 2002 on account of a sharp weather-related drop in agricultural output. The IMF staff supports the government's reform strategies in the electricity and groundnut sectors, as well as the ongoing reforms in the postal, and public and private pension systems.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet